1991
DOI: 10.1090/s0002-9939-1991-1047003-9
|View full text |Cite
|
Sign up to set email alerts
|

On a differential equation for Koornwinder’s generalized Laguerre polynomials

Abstract: Abstract.Koornwinder's generalized Laguerre polynomials {L°' (x)}^=0 are orthogonal on the interval [0, oo) with respect to the weight function r,'+|.xae~j: + Nô(x), a > -1 , N > 0. We show that these polynomials for N > 0 satisfy a unique differential equation of the form

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 7 publications
5
48
0
Order By: Relevance
“…Later many contributions in this direction were made by T. Koornwinder [28], L. Littlejohn [30], J. Koekoek, R. Koekoek [27], etc. In recent times there is much activity in generalizations and versions of the classical result of Bochner, see, e.g., [17,18,20,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Later many contributions in this direction were made by T. Koornwinder [28], L. Littlejohn [30], J. Koekoek, R. Koekoek [27], etc. In recent times there is much activity in generalizations and versions of the classical result of Bochner, see, e.g., [17,18,20,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In [5] J. Koekoek and R. Koekoek showed that the polynomials {L%'M(x)}™=0 satisfy a unique differential equation of the form…”
Section: Introductionmentioning
confidence: 99%
“…So, the example analyzed in this paper (semiclassical Jacobi-type OP with respect to a moment functional of class s = 4) is, probably, a good starting point, since other semiclassical cases like Laguerre-type, Hermite-type (see Álvarez-Nodarse and Marcellán, 1995;Koekoek and Koekoek, 1991;Koekoek, 1988), and, of course, the very classical OP should be connected by limit transitions to the semiclassical Jacobi-type OP as the starting family. The present paper helps us to understand the analysis of semiclassical OP (very close to the classical ones), and then one has a good basis for studying other extensions, for which there are quite a few possibilities for research.…”
Section: Conclusion and Open Problemsmentioning
confidence: 92%
“…Also the particular cases of the Krall-type polynomials (A. M. Krall, 1981; H. L. Krall, 1940) have been obtained from this general case as special cases or limit cases. The Laguerre case was considered in detail in Koekoek and Koekoek (1991), Koekoek (1988Koekoek ( , 1990.…”
Section: Introductionmentioning
confidence: 99%